Permanence of a Discrete Nonlinear Prey-Competition System with Delays - Hongying Lu (Discrete Dynamics in Nature and Society)
A discrete nonlinear prey-competition system with m-preys and (n-m)-predators and delays is considered. Two sets of sufficient conditions on the permanence of the system are obtained. One set is delay independent, while the other set is delay dependent.